2009
DOI: 10.1007/s10103-009-0698-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of the pulsed dye laser 585 nm versus 595 nm in the treatment of new surgical scars

Abstract: after laser irradiation, the treated sections were more similar to a non-scarring process than the control. Cosmetic outcome: visual analog scales increased in all groups (P < 0.05), but the greatest increases were observed in the 585 nm and 595 nm laser-treated groups (50% and 60%, respectively) compared with controls (30%). There were significantly higher scores with the lasers than for the control (P < 0.001) at each visit after baseline. Both the 585 nm and 595 nm PDL treatments were effective in improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…9,30,31 Although this study was not powered to examine differences between older and younger scars, we found that the PhGA of four of five scars younger than 6 months had greater improvement of the treated side than of the untreated control side at 3-month follow up. 9,30,31 Although this study was not powered to examine differences between older and younger scars, we found that the PhGA of four of five scars younger than 6 months had greater improvement of the treated side than of the untreated control side at 3-month follow up.…”
Section: Subanalysis Of Scars Younger Than Six Monthsmentioning
confidence: 76%
“…9,30,31 Although this study was not powered to examine differences between older and younger scars, we found that the PhGA of four of five scars younger than 6 months had greater improvement of the treated side than of the untreated control side at 3-month follow up. 9,30,31 Although this study was not powered to examine differences between older and younger scars, we found that the PhGA of four of five scars younger than 6 months had greater improvement of the treated side than of the untreated control side at 3-month follow up.…”
Section: Subanalysis Of Scars Younger Than Six Monthsmentioning
confidence: 76%
“…[22][23][24] At the final evaluation visit, there was a trend toward a significant difference between groups in VSS total score, with the nonpurpuric segments rated as better than the other conditions, although all scar segments improved over time, whether treated or not, when evaluated using global cosmetic ratings. Although this may seem surprising, it confirms the results of several other studies that used PDL with lowerenergy nonpurpuric parameters and showed significant improvements in scar appearance.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have evaluated intervention for scar remodeling starting as early as 2 weeks after the surgical procedure [4,26]. Thus, further prospective studies are warranted to decipher if there is an optimal time to improve scar remodeling.…”
Section: Discussionmentioning
confidence: 99%